Clinical and translational science award T32/TL1 training programs: program goals and mentorship practices. Issue 1 (27th December 2022) - Sancheznieto, Fátima; Sorkness, Christine A.; Attia, Jacqueline; Buettner, Kathryn; Edelman, David; Hobbs, Stuart; McIntosh, Scott; McManus, Linda M.; Sandberg, Kathryn; Schnaper, H. William; Scholl, Linda; Umans, Jason G.; et al.
Abstract: Introduction: A national survey characterized training and career development for translational researchers through Clinical and Translational Science Award (CTSA) T32/TL1 programs. This report summarizes program goals, trainee characteristics, and mentorship practices. Methods: A web link to a voluntary survey was emailed to 51 active TL1 program directors and administrators. Descriptive analyses were performed on aggregate data. Qualitative data analysis used open coding of text followed by an axial coding strategy based on the grounded theory approach. Results: Fifty out of 51 (98%) invited CTSA hubs responded. Training program goals were aligned with the CTSA mission. The trainee population consisted of predoctoral students (50%), postdoctoral fellows (30%), and health professional students in short-term (11%) or year-out (9%) research training. Forty percent of TL1 programs support both predoctoral and postdoctoral trainees. Trainees are diverse by academic affiliation, mostly from medicine, engineering, public health, non-health sciences, pharmacy, and nursing. Mentor training is offered by most programs, but mandatory at less than one-third of them. Most mentoring teams consist of two or more mentors. Conclusions: CTSA TL1 programs are distinct from other NIH-funded training programs in their focus on clinical and translational research, cross-disciplinary approaches, emphasis on team science, and integration of multiple trainee types. Trainees in nearly all TL1 programs were engaged in all phases of translational research (preclinical, clinical, implementation, public health), suggesting that the CTSA TL1 program is meeting the mandate of NCATS to provide training to develop the clinical and translational research workforce.